A digital atlas of middle to large brain vessels and their relation to cortical and subcortical structures - Roberto eViviani; Roberto eViviani (Frontiers Media S.A., 2016)
While widely distributed, the vascular supply of the brain is particularly prominent in certain anatomical structures because of the high vessel density or their large size. A digital atlas of middle to large vessels in Montreal Neurological Institute coordinates is here presented, obtained from a sample of N = 38 healthy participants scanned with the time-of-flight magnetic resonance technique, and normalized with procedures analogous to those commonly used in functional neuroimaging studies. Spatial colocalization of brain parenchyma and vessels is shown to affect specific structures such as the anteromedial face of the temporal lobe, the cortex surrounding the Sylvian fissure, the anterior cingular cortex, and the ventral striatum. The vascular frequency maps presented here provide objective information about the vascularisation of the brain, and may assist in the interpretation of data in studies where vessels are a potential confound.